"Continuously struggling for balance": The lived experiences of Dutch parents caring for children with profound intellectual and multiple disabilities. Issue 2 (3rd April 2023) - Geuze, Liesbeth; Goossensen, Anne; Schrevel, Samuel
ABSTRACT: Background: Parents of children with profound intellectual and multiple disabilities (PIMD) have extensive care duties. This study describes the phenomenon "parenting a child with PIMD." Method: We conducted in-depth interviews with 25 Dutch parents. A reflective lifeworld research was used. Findings: The essential meaning of the phenomenon was understood as "continuously struggling to create and maintain new equilibriums that protect the child and the family from hardship; changing in context through time." The following eight constituents were identified: (1) medical complexity; (2) multidimensional weariness; (3) care for siblings; (4) social connectedness; (5) uncertainty about the future; (6) wrecking bureaucracy; (7) dependency on healthcare delivery; and (8) financial concerns. Conclusions: Healthcare services should provide families with easy access to assistive technology and services needed to manage family life. Responsiveness to parents' challenges offers them the possibility to participate in society. Healthcare professionals should address the parents' perspectives related to the child's quality of life.